Activism as a pathway to global citizenship. Issue 2 (1st June 2017) - Reysen, Stephen; Hackett, Justin
Abstract: We examined the influence of prior work with activist issues on the antecedents, identification, and outcomes of global citizenship. Participants rated their engagement with activist issues and measures related to global citizenship identification antecedents and outcomes. The results showed that engagement with activist issues predicted global citizenship through the perceptions of one's normative environment and global awareness. Activism also indirectly predicted prosocial values and behaviors related to global citizen identity through antecedents and global citizenship identification. The results highlight the prosocial outcomes of participation in activist movements.